2005
DOI: 10.1149/1.1924308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Implanted Cl and Deposited Oxides on the Pitting Behavior of Aluminum

Abstract: Insight into the influence of Cl on the pitting behavior of aluminum has been gained using a combination of ion implantation and oxide deposition. High-purity Al thin-film samples were implanted with 35 keV Cl + followed by plasma deposition of an aluminum oxide ͑Al 2 O 3 ͒. The pitting potential of unimplanted areas in 50 mM NaCl increased with increasing deposited oxide thickness ͑0, 80, 140 Å͒. For implanted areas, polarization in 50 mM NaCl resulted in pitting that was insensitive to oxide thickness and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…For instance, using anodic polarization method, Serna et al found the pitting potential of Al 2 O 3 surface has relationship with the oxide film thickness, both a critical Cl − distribution and oxide modification are contributing factors to pit nucleation [11]. Voltammetric anodic growth curves were performed by Boxley et al to report the dissolution rate of the Al 2 O 3 film in 0-150 mM NaCl solution.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using anodic polarization method, Serna et al found the pitting potential of Al 2 O 3 surface has relationship with the oxide film thickness, both a critical Cl − distribution and oxide modification are contributing factors to pit nucleation [11]. Voltammetric anodic growth curves were performed by Boxley et al to report the dissolution rate of the Al 2 O 3 film in 0-150 mM NaCl solution.…”
Section: Introductionmentioning
confidence: 99%
“…After atmospheric corrosion, ACSR conductor mechanical properties and electrical properties are reduced, and may lead to line broken stocks, bolt, or even a power outage accidents. Himself at home and abroad such as aluminium and its alloy and zinc on corrosion behavior under different atmospheric corrosion medium to carry out the more basic research [1][2][3], but due to the complexity of ACSR conductor composition and structure, the composition of the corrosion behavior and corrosion products, structure more complicated [4].For the first time under laboratory conditions, such as through a cyclical wet/dry salt spray environment under the accelerated corrosion test to study the corrosion behavior of aluminum, steel and galvanized steel, based on the mass loss of the wire to evaluate degree of atmospheric corrosion of the wire, start the transmission wire corrosion behavior of laboratory research by Wang, etc [5]. Zhengyao [6] has been adopting NaHSO3 + NaCI to zinc ion in aqueous solution and aluminum alloy atmospheric corrosion process of research, the main research results and field exposure experiment results are identical with each other [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Implantation of chlorine into the Al oxide and the oxide/metal interface was introduced as one alternative way to validate importance of the chloride incorporation mechanism [20][21][22] . It was shown that in a chloride-free environment pitting takes place on Cl + -implanted Al samples only for a chlorine distribution above some critical value [20][21][22] . The average pitting potential as a measure of the pitting susceptibility decreases with an increase of the chlorine incorporated in the oxide 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the ion implantation technique has been introduced in studies of pitting corrosion 19 . Implantation of chlorine into the Al oxide and the oxide/metal interface was introduced as one alternative way to validate importance of the chloride incorporation mechanism [20][21][22] . It was shown that in a chloride-free environment pitting takes place on Cl + -implanted Al samples only for a chlorine distribution above some critical value [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%